Total Quality Management in Insurance: Companies Field Study in Iraqi Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2012)
Total quality management is considered a modern management concept that achieved success in all fields of various industrial and service sectors in advanced countries . One of these sectors is insurance. This concept aims at improving and developing the performance of insurance service continually . It is the gate that can enable radical change in the organization culture inside the company to transform it from using the traditional management style into using the modern style which achieves high quality standard of insurance service . As a result many insurance companies headed to applying the principles of total quality management in their companies . This study aims at raising the standard of the performance of the Iraqi Insurance Company and at the Continual improvement of the insurance service presented to the insured . The study was applied in the Iraqi Insurance Company by testing a sample of (32) workers in the Company . A questionnaire was used to gather the data . The study reached a number of conclusions . One of the most important conclusion is that the principles of total quality management are applied in the Iraqi Insurance Company in an acceptable way and that the company should do more to enforce that . The researcher submitted a group of recommendations to the company based on the conclusions the study reached. The high management in the company issues a decree to rely on total quality management approach  .